CHARACTERISTIC OF INFLUENZA VIRUS H5N1 FROM LAYER POULTRY FARM LEGOK DEMARCATION, SERANG DISTRICK, BANTEN - Abharina, Nurfildza Wafeta; Kencana, Gusti Ayu Yiniati; Wandia, I Nengah (Buletin Veteriner Udayana, 2023)
Avian Influenza virus infection is still a serious concern in the poultry sector in Indonesia. The molecular character of the AI virus that easily mutates is thought to be a factor in the AI virus continuing to spread and having endemic status. This study aims to characterize the Avian Influenza virus from laying poultry in Legok District, Serang Districk, Banten as a form of preparation for the AI H5N1 vaccine. The test sample used is a collection of isolates owned by PT. Sanbio Laboratories, Bogor with the name Legok isolate. This study used two comparator isolates, namely Sukoharjo isolate (A/Duck/Sukoharjo/BBVW-1428/2012) and Garut isolate (A/Chicken/Garut/BBVW-223/2007) which are the master seeds of the local AI H5N1 vaccine. Virus isolation was carried out on embryonated chicken eggs (TAB) aged 9 days and then the virus isolation results were tested using the fast and slow hemagglutination (HA) test to detect the presence of the virus, the Reverse Transcritase Polymerase Chain Reaction (RT-PCR) test was used to see AI virus subtypes and then confirmed by sequencing tests to see the genetic distance and kinship between the isolates tested. The result is that Legok isolate is in the same clade as Sukoharjo isolate, which is in clade 2.3.2, but Legok isolate forms a new subclade 2.3.2 variant, while Garut isolate is in clade 2.1.3. The genetic distance for each isolate obtained was that Legok isolate to Sukoharjo isolate had a genetic difference of 3%, homology 97%, Legok isolate to Garut isolate had a genetic difference of 11.5%, 88.5% homology while Sukoharjo isolate to Garut isolate the genetic difference is 9% and the homology is 91%. The conclusion is that the Legok isolate has different characteristics from the Sukoharjo isolate and the Garut isolate. This indicates that the Legok isolate has a mutation, so it is necessary to carry out monitoring and further research for vaccine seeds from Legok isolate .